GIMP bible - Van Gumster, Jason (Wiley, 2010)
"GIMP is a free, Photoshop-like image manipulation program, and as its use grows, so does the demand for detailed instruction on how to get the very most out of it. GIMP Bible is the most comprehensive and current independent GIMP reference available that goes beyond official documentation. If you're a digital artist or photographer, the step-by-step explanations in this authoritative guide show you how to power-use GIMP throughout a production pipeline. Topics include understanding the GIMP interface and how to work with it, how to use all of GIMP's tools to create high-quality images, GIMP's default filters and plug-ins, advanced techniques for customization with Python and Scheme scripting, and much more. Get the most out of this free image editing tool for your production pipeline with the GIMP Bible"--Resource description page.
Print version record
Keywords: GIMP (Computer file); Computer graphics; Infographie; computer graphics; COMPUTERS; Computer Graphics